A Review of Abisko Case Study: Recent and Past Trees and Climates at the Arctic/Alpine Margin in Swedish Lapland - Leif Kullman (Challenging Issues on Environment and Earth Science Vol. 2, 2021)
For about a century, Abisko Scientific Research Station in northern Swedish Lapland has served as a logistic base for high-quality geoecological research in subalpine/subarctic environments. In recent years, and driven by the prospect of alleged man-made global warming, much of the scientific focus has been on dynamics of the treeline ecotone. In this context, field observations, analyses and interpretations emanating from research carried out in the Abisko region are discussed in perspective of recent observations and analyses. Local mountain birch (Betula pubescens ssp. czerepanovii) treeline rise by maximum 230 m during the past 100 years conforms quantitatively to data obtained further south in the Scandes. This broad-scale inter-regional coincidence indicates that a common operative agent has been responsible. The most likely candidate is recorded secular climate warming by 2.5°C. This contention is further supported by age structure analysis in the birch treeline advance zone, indicating that the vegetative initiation of new trees peaked during the warm 1930s, when reindeer number were high and reached a nadir during the relatively cold 1960s and 1970s, coincident with smaller reindeer herds. These data suggest, contrary to previous hypotheses, stating that, relative to climate change, intensity of reindeer browsing has been of minor importance for birch treeline dynamics. The upper limit of closed stands of mountain birch and pine have shifted relatively insignificantly in elevational position during the predominantly warm past 100 years. Over the same period or longer, common aspen (Populus tremula) has frequently occurred as low-growing krummholz (stunted growth forms) over the entire mountain birch region. During the warm 1930s and just like birch, rapid height increment was initiated and has continued up to the present day. Thereby, many individuals have attained tree-sized in recent decades. Accordingly, aspen (Populus tremula) has, presumably in response to climate warming, become a more conspicuous element in the mountain birch forest. The current analyses refute prior claims that aspen regeneration is accomplished by seed regeneration rather than phenotypic adjustment of old-growth creeping individuals. Picea abies and Larix sp. are recorded as new species in the Abisko area. In accordance with prior analyses in other parts of the Scandes, megafossil data show that the treelines of Scots pine (Pinus sylvestris), mountain birch (Betula pubescens ssp. czerepanovii) and grey alder (Alnus incana) peaked in the early Holocene. Based on the elevational difference between early Holocene and present treeline positions (adjusted for 100 m land uplift) it may be inferred that the summer temperatures exceeded those of the last few decades by about 3.0°C. This study challenges recent proposals that aspen is currently spreading upslope and westwards in the birch forest belt by seed establishment of new individuals. In response to recent warming they have attained tree size and have become a more conspicuous element of the landscape.